The interactive effects of stress and coping style on cognitive function in patients with schizophrenia - Zhu X (Dove Medical Press, 2019)
Xiaodan Zhu,1 Xuebing Xu,2 Chao Xu,2 Jingyi Zhang,2 Xiaofeng Zhang,2 Li Ma,2 Juan Liu,3 Kefang Wang11Devision of Nursing Fundamentals, School of Nursing, Shandong University, Shandong, China; 2Inpatient Department, Ningxia Mental Health Center, Ningxia Ning–An Hospital, Ningxia, China; 3Devision of Humanities, School of Nursing, Ningxia Medical University, Ningxia, China Purpose: Previous studies have not determined the interactive effects of stress and coping style on cognitive function in patients with schizophrenia, and the current studies have been restricted to the relationship between stress and stress response, which may be associated with cognitive impairment in individuals with schizophrenia. The present research was aimed to determine whether stress is related to cognitive function in patients with schizophrenia. In addition, this research further investigates the moderating effects of coping style on the relationship between stress and cognitive function in patients with schizophrenia on the basis of stress and coping theory.Patients and methods: Our sample consisted of 274 patients with a confirmed diagnosis of schizophrenia, and all of them completed the Simple Cope Style Questionnaire, Social Readjustment Rating Scale, and cognitive function assessment. A multivariate regression analysis was performed to investigate the possible correlations between cognitive function and stress, and the moderating effects of coping style on the relationship between stress and cognitive function were tested using the PROCESS macro for SPSS.Results: Stress was negatively correlated with working memory. Negative coping but not positive coping moderated the relationship between stress and working memory in patients with schizophrenia, and the Johnson–Neyman technique showed that the moderating effect was significant only above this cutoff (38.32% of all negative coping scores). This means that when exposed to similar stress, patients adopting high negative coping had worse working memory than those who did not.Conclusion: These findings suggested that the assessment of stress and coping style may help estimate working memory impairment risk in patients with schizophrenia, and reducing negative coping may be a crucial intervention target to prevent further impairment of working memory in patients with schizophrenia suffering from great stress. Keywords: cognitive function, life events, negative coping, positive coping